Utilization of Biomass to Ash: An Overview of the Potential Resources for Alternative Energy - Natt Makul (MDPI AG, 2021)
Climate change and the potential depletion of fossil fuels have increased international demand for alternative and renewable energy sources. In terms of the energy sector, for example, most of the South-East Asian countries (SACs) have a large number of biomass sources due to their vast forest resources and agriculture-based economies. Thus, the critical review was aimed at highlighting the overview of biomass energy in South-East Asia as a dynamically developing region, in order to obtain economic and environmental benefits from the existing sources of biomass in the world. The current review analyzed the sources of biomass, as well as their energy potential, use, and management, based on reports from different countries, published studies, and scientific articles. In SAC, the main sources of biomass were found to be coconut residues, oil palm residues, sugar cane residues, rice straw, rice husks, wood waste, and firewood. The combined annual biomass potentials in the forestry and agricultural sectors in South-East Asia were approximately over 500 million tons per year and more than 8 gigajoule of total energy potentials. The study identified the challenges and barriers to using biomass in these countries to achieve sustainable use of biomass sources and recommended sustainable approaches to using biomass energy by comparing traditional uses of biomass. Smart grid technologies have ways for solutions for better electric power production and efficient ways for distribution and transmission of electricity. Smart grids require less space and can be more easily installed when compared to traditional grids because of their versatilities. Upcoming challenges include technology optimization for the following uses of biomass energy: direct combustion of woody biomass; pyrolysis and gasification of biomass; anaerobic digestion of organic waste to produce biogas; landfill gas production direct incineration of organic waste. The barriers in this technology are emissions of carbon and nitrogen oxides, unpleasant odors, as well as the uncontrolled harvesting of biomass, which can harm nature.